Compounding impacts of climate change and urbanisation on water-energy-food Nexus in global south countries. A systematic review - Taiwo Temitope Bamgboye; Tamara Avellán; Björn Klöve; Ali Torabi Haghighi (Environmental and Sustainability Indicators)
As climate change and urbanisation continue to reshape global resource demand and supply, Global South countries face compounded challenges in managing the interconnected water, energy, and food (WEF) nexus. This systematic review assessed the current state of research on their combined impact across Africa, Asia, Latin America, and the Caribbean, analysing 75 peer-reviewed articles published between 2011 and 2023. Key findings include the following: (1) No literature was found analysing the WEF Nexus, climate change, and urbanisation. This gap suggests that policymakers and resource managers may lack full understanding of their combined impact on WEF insecurities. (2) Climate change primarily affects resource supply through biophysical impacts, while urbanisation through socioeconomic impacts influences resource demand and consumption patterns. Together, these two disrupt the balance between supply and demand, increasing insecurities across the WEF elements. (3) In addition, governance issues such as weak systems, siloed government structures, and low political will hinder effective WEF nexus management. (4) Qualitative methods were the most prominent in studying both problems, suggesting a focus on contextual understanding. (5) Distinctively, no existing solutions simultaneously address the impact of climate change and urbanisation on the WEF nexus. The proposed solutions to these impacts tend to target one driver in isolation, such as renewable energy for climate mitigation, or urban agriculture for urban resilience. This review highlights the need to address the compounding impact of these problems to ensure an equilibrium between supply and demand in the face of global environmental changes.